Hubungan Antara Tingkat Pendidikan dan Status Ekonomi pada Penderita Low Back Pain - Kartika Agung Kurniawan; Nurul Halimah; Mey Jeni Mafroh Hasibuan; Ichwanushofa Ramadani (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Low back pain (LBP) is one of the most common musculoskeletal complaints and is influenced by sociodemographic factors, including education level and economic status. Objective: This study aimed to determine the relationship between education level and economic status among patients with low back pain. Methods: A descriptive-analytic cross-sectional study was conducted among 50 LBP patients at Physiomar Clinic and Rehab.in Clinic, selected through consecutive sampling. Education level and economic status based on monthly household income were collected using a questionnaire. Data were analysed using the Chi-square test, Fisher's exact test, and Spearman's rank correlation. Results: Most respondents had low or secondary education (36.0% each), while 52.0% had a middle economic status. Low education was significantly associated with low economic status (Fisher's exact test, p < 0.001; OR = 108.5; 95% CI: 9.6–475.5). Education level was strongly correlated with monthly income (rho = 0.947; p < 0.001). Education and income were also negatively correlated with NRS pain scores (rho = -0.851 and rho = -0.806, respectively; both p < 0.001). Conclusion: Lower education and economic status were closely interrelated among LBP patients and were associated with greater pain severity. Targeted ergonomic education, health-literacy support, and improved access to physiotherapy are needed for vulnerable groups.